Dual effects of quercetin on contraction in cardiac and skeletal muscle preparations - Apisariyakul A. (2014)
The effects of quercetin, a plant flavonoid, on contraction in cardiac and skeletal muscle preparations were examined. Higher concentrations of quercetin increased mean arterial blood pressure in anesthetized rats. Quercetin showed positive inotropic action on spontaneous contraction in a dose-dependent manner in isolated rat atria. Quercetin prevented the negative inotropism evoked by acetylcholine in isolated rat atria. On the other hand, quercetin inhibited the twitch contraction in isolated rat hemidiaphragm muscles. The addition of Ca2+ to extracellular medium recovered the inhibitory effects of twitch contraction in Ca2+-free medium but did not prevent the inhibitory effects of twitch contraction in Ca2+-free medium containing quercetin. The present results suggest that quercetin have a positive inotropic action in cardiac muscle but inhibitory effects on contraction in skeletal muscle.